Artificial Intelligence in E-commerce: The Impact of Consumer Behavior on Purchasing Decisions - Maliana Puspa Arum; Silvia Van Marsally; Chusnul Maulidina Hidayat (Lembaga Pengembangan Kinerja Dosen, 2026)
The development of Artificial Intelligence (AI) has made this technology a strategic component in e-commerce management through the transformation of digital marketing practices and consumer interactions. The application of AI enables companies to improve personalization, service efficiency, and the quality of consumer experiences through recommendation systems, chatbots, virtual agents, and AI-based content. This study aims to systematically examine the role of Artificial Intelligence in e-commerce and its impact on consumer behavior in the purchasing decision-making process. The research method used is a literature review with a qualitative descriptive approach to national and international journal articles published in the period 2019–2025. Selected articles are analyzed thematically to identify patterns of AI implementation, consumer behavioral responses, and their implications for purchasing decisions. The results of the study indicate that AI has a positive effect on consumer trust, satisfaction, and purchase intention by increasing information relevance, service speed, and marketing personalization. However, issues of data privacy, perceived authenticity, and limited empathy in AI-based interactions have the potential to affect consumer loyalty. Therefore, a hybrid approach that combines the sophistication of AI with human interaction is recommended to create a sustainable consumer experience in the e-commerce ecosystem.